The effect of accounting-based debt covenants on equity valuation - Core, John E.; Schrand, Catherine M. (Journal of Accounting and Economics, 1999)
We use an option pricing framework to model equity valuation when firms face costs associated with violating accounting-based debt covenants. Our model shows that the value of equity depends on two factors: the economic value of the firm and the probability that the firm violates the covenant. Consistent with the model's prediction that the `covenant' effect is greatest for firms near covenant violation, we find that responses to earnings that are less informative about future cash flows (losses and transitory earnings) are significant only for thrift institutions that are near violation of regulatory net worth covenants.